2016
DOI: 10.1007/978-3-319-31973-5_4
|View full text |Cite
|
Sign up to set email alerts
|

Mesonephric Cell Migration into the Gonads and Vascularization Are Processes Crucial for Testis Development

Abstract: Testis morphogenesis requires the integration and reorganization of multiple cell types from several sources, one of the more notable being the mesonephric-derived cell population. One of the earliest sex-specific morphogenetic events in the gonad is a wave of endothelial cell migration from the mesonephros that is crucial for (1) partitioning the gonad into domains for testis cords, (2) providing the vasculature of the testis, and (3) signaling to cells both within the gonad and beyond it to coordinately regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 146 publications
(178 reference statements)
0
5
0
Order By: Relevance
“…Transcriptional activation of the Kdr gene by WT1 is a novel finding that deserves more careful consideration. Previous studies identified VEGFA as a critical regulator of the sex-specific vascularization that is crucial for seminiferous cord formation in the developing testis (15,16,47). During this process, KDR-positive endothelial cells are recruited to migrate from the adjacent mesonephros into the testis, where they provide the vasculature and partition the gonad into domains for the seminiferous cords (16) (reviewed in Ref.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transcriptional activation of the Kdr gene by WT1 is a novel finding that deserves more careful consideration. Previous studies identified VEGFA as a critical regulator of the sex-specific vascularization that is crucial for seminiferous cord formation in the developing testis (15,16,47). During this process, KDR-positive endothelial cells are recruited to migrate from the adjacent mesonephros into the testis, where they provide the vasculature and partition the gonad into domains for the seminiferous cords (16) (reviewed in Ref.…”
Section: Discussionmentioning
confidence: 99%
“…During this process, KDR-positive endothelial cells are recruited to migrate from the adjacent mesonephros into the testis, where they provide the vasculature and partition the gonad into domains for the seminiferous cords (16) (reviewed in Ref. 47). At later stages, KDR-expressing cells are dispersed around the seminiferous cords (15,16).…”
Section: Discussionmentioning
confidence: 99%
“…SRY transcription is limited in time and space [38,39,42], but it presents multiple and prolonged effects during the differentiation of the male gonad due to the activation of multilayered downstream pathways. SRY expression begins in the centre of the gonad, spreading towards the pole in a wave, paracrine fashion [34,43,44]. Of note, in the bipotential gonad, both the male and female determining genes are expressed at similar levels [40].…”
Section: The Determination Of the Normal Gonadal Patternmentioning
confidence: 99%
“…At the moment of gonadal differentiation, SOX9 expression is raised in male embryos, but maintained in residual levels in females [45]. Since the precursor cell types are similar in the bipotential gonads of both female and male embryos [43], once the fate of the supporting cells is established, it orchestrates the differentiation of all other cell lineages in the gonad [49].…”
Section: What Might Go Wrong In the Ovarian Development In 78xx;sry-mentioning
confidence: 99%
“…Another possibility is that NGFR + /PDGFRα + cells might appear during culture due to the phenomenon of endothelial to mesenchymal transition (EndMT). This is an important developmental mechanism where endothelial cells transdifferentiate into MSCs in various tissues, (reviewed in 37 ), including the testis, 38‐40 but can also occur in endothelial cells in vitro 41 . Whether EndMT also plays a role in Leydig cell development in vitro and/or in vivo needs further investigation.…”
Section: Discussionmentioning
confidence: 99%